Aportaciones al conocimiento de la flora del macizo de Sierra Arana (Granada, España). - Fuentes-Carretero, Julián Manuel (Acta Botanica Malacitana, 2014)
Contributions to the knowledge of the flora of the Sierra Arana (Granada, Spain) Palabras clave. Flora, corología, novedades, Andalucía. Key words. Flora, chorology, new records, Andalusia.